Bhairawa Puja Ritual Practice in Pujungan Bali - Nasution, Nasution (Paramita: Historical Studies Journal, 2022)
This research examines the Puja Bhairawa teachings development in Hindu Bhairawa in Pujungan Bali, especially the stages of ritual transformation and traces of the remaining practices of them which are still carried out as the Indonesian society traditions. The Research Methods include interview, observation, and documentation. The research results are the remaining teachings of the Pancamakara Puja practice that still exist such as Bhairawa puja ritual in Pujungan Bali. Hindu Bhairawa in Pujungan was brought to life by a man named I Nengah Gatot Kaca. The Bhairawa puja ritual is used as a short cut problem weapon to solve world problems. The Bhairawa puja ritual at Pujungan is placed in a quiet Pujungan coffee garden area away from the crowds. The ceremony leader of the ritual is I Nengah Gatot Kaca/Gede Gatot Bhinawa Rata who has the title of Diksa Bheru Baba. In the coffee garden area, two black stones (linggams) were placed as the embodiment of Bhairava and Bhairavi. The Bhairawa puja ritual procession began with prepare ritual facilities for male goat blood, alcohol, flowers, fruits and other ingredients. After all the ritual facilities were ready and the ritual participants were present, the ritual procession begins by summoning the spirits of Bhairawa and Bhairawi which was done by making offerings such as the blood of a sacrificial animal which is sprinkled on two lingams as the embodiment of Bhairava and Bhairavi while accompanied by chanting of mantras by the priest, followed by other offerings such as alcoholic beverages, fragrances, and flowers on the Linggam. At that time, some participants will feel the presence of Bhairava and all ritual participants can do whatever prayer or invocation they want.Penelitian ini mengkaji perkembangan ajaran Puja Bhairawa dalam Hindu Bhairawa di Pujungan Bali, khususnya tahapan transformasi ritual dan jejak sisa praktiknya yang masih dilakukan sebagai tradisi masyarakat Indonesia. Metode Penelitian meliputi wawancara, observasi, dan dokumentasi. Hasil penelitian adalah sisa ajaran dari praktik Puja Pancamakara yang masih ada seperti ritual puja Bhairawa di Pujungan Bali. Bhairawa Hindu di Pujungan dihidupkan kembali oleh seorang pria bernama I Nengah Gatot Kaca. Ritual puja bhairawa digunakan sebagai senjata jalan pintas untuk memecahkan masalah dunia. Ritual puja Bhairawa di Pujungan ditempatkan di area kebun kopi Pujungan yang tenang jauh dari keramaian. Pemimpin upacara ritual tersebut adalah I Nengah Gatot Kaca/Gede Gatot Bhinawa Rata yang bergelar Diksa Bheru Baba. Di areal kebun kopi ditempatkan dua buah batu hitam (linggam) sebagai perwujudan Bhairava dan Bhairavi. Prosesi ritual puja bhairawa dimulai dengan menyiapkan sarana ritual untuk darah kambing jantan, alkohol, bunga, buah-buahan dan bahan lainnya. Setelah semua sarana ritual siap dan peserta ritual sudah hadir, prosesi ritual dimulai dengan pemanggilan arwah Bhairawa dan Bhairawi yang dilakukan dengan cara memberikan sesaji berupa darah hewan kurban yang dipercikkan pada dua lingam sebagai perwujudan dari Bhairava dan Bhairavi sambil diiringi dengan pembacaan mantra oleh pendeta, dilanjutkan dengan sesaji lainnya seperti minuman beralkohol, wewangian, dan bunga di Linggam. Pada saat itu, beberapa peserta akan merasakan kehadiran Bhairava dan semua peserta ritual dapat melakukan doa atau doa apa pun yang mereka inginkan.Cite this article: Nasution. (2022). Bhairawa Puja Ritual Practice in Pujungan Bali. Paramita: Historical Studies Journal, 32(1), 97-106. http://dx.doi.org/10.15294/paramita.v32i1.22580